Thermorheological behavior of various long-chain branched polyethylenes - Stadler, Florian; Kaschta, Joachim; Münstedt, Helmut (Macromolecules, 2008)
To analyze the thermorheological behavior of various polyethylenes, the relaxation spectra were shifted. Not only linear and short-chain branched PE but also the classical high-pressure LDPE were found to be thermorheologically simple, i.e., the activation energy E(a) is independent of the relaxation strength or the relaxation time, respectively. However, for the long-chain branched metallocene catalyzed polyethylenes investigated a significant dependence of the activation energy E(a) on the relaxation time is detected. At shorter relaxation times E(a) is very close to that of linear PE, but it increases with longer times. The lower E(a) values are assumed to be due to linear molecules and the higher ones to different species of long-chain branched molecules. These findings offer the possibility to use the analysis of the thermorheological complexity to get an insight into the branching structure of polyethylenes. For the LCB-mPE investigated, it can be concluded that they are a mixture of linear and long-chain branched chains.